Development of microemulsions and self-emulsifying systems for oral drug delivery - Adamczyk, Bożena E. (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2012)
The main aim of the current work was to explore microemulsions (ME) and self- emulsifying lipid formulations (SELFs) comprising derivatives of capric/caprylic acids (Captex 355, Captex 200P, Capmul PG-8, Capmul MCM) as drug delivery systems for oral administration of hydrophilic compounds (BCS class III) intended for encapsulation. Physicochemical profiling of hydrophilic model compounds (two bisphosphonates: sodium alendronate trihydrate and disodium pamidronate pentahydrate and a decaptide, acyline monoacetate) was carried out. Sodium alendronate trihydrate and disodium pamidronate pentahydrate were found to be highly water soluble with the highest solubility achieved in the modified K-Mcllvaine’s buffers pH 7.8 (~52 mg/ml) and pH 4.4 (~70 mg/ml) respectively. Acyline monoacetate was found to be also highly water soluble, however rapid gelation (physical instability) was observed in aqueous solutions. Good solubility (up to 10 mg/g) and physical stability (lack of gelling) was observed in propylene glycol and the standard GIPET® II formulation. The isoelectric point of acyline was found to be ~11.4.
Keywords: Pharmacy & Pharmaceutical Sciences, Ph.D.; Ph.D. Trinity College Dublin